Utilization of Recent Technologies for Future Dentist Training - KaVo PREPassistant - T. Sojka (Czech Dental Chamber, 2008)
Methodics of scanning, 3D projection and evaluation of artificial teeth preparations. Quality assessment of scanning and comparison with digital photograph.